Analisis Penyerapan Tenaga KerjaDi Eks-Karisidenan SurakartaTahun 2010-2014 - Nur Istanto, Adnan; , Ir. Maulidyah Indira Hasmarini M.Si (2017)
This study aims to analyze the influence of Minimum Wage (UMK), Economic Growth (PDRB), investment and inflation on the absorption of manpower in ekskarisidenan Surakarta The data used is panel data by taking 7 districts / cities contained in Karisidenan Surakarta with time frame 5 years (2010-2014). Through secondary data taken from literature study both BPS literature, previous journal and research. The data is processed by using panel data with selected method that is Fixed Effect Model (FEM) analysis method assisted with E-views7 software in its operation. The results of this study indicate that economic growth (GRDP) and investment variables significantly influence the level of employment absorption in Surakarta ex-karisidenan 2010-2014 period at a significance level of 5%. While the Inflation and Minimum Wage (UMK) variables did not significantly influence the unemployment rate in Eks-karisidenan Surakarta 2010-2014 period at the level of 10% significance.